PERAN GURU DALAM MEMBENTUK KARAKTER DISIPLIN ANAK SEKOLAH DASAR - Malidina Firah Dina; Nurul Makkiyah; Ana Naimatul Jannah; Nurhalima (STKIP Subang, 2025)
This research is motivatied by the ongoing issue of indisciple among elementary school students, such as arriving late, not completing assignmments, and violating school rules, even though discipline is a key factor is achieving academic success and character development. The aim of this study is to determine the role of teachers in shaping the disciplinary character of fifth-grade students at UPTD SDN Tanjung Jati 2, including the strategies implemented, supporting factors, and challenges faced. The research method used is descriptive qualitative, with data collection through observations, in-depth interviews with teachers and students, as well as documentation. The results of the study show that teachers play a very dominany role not only as educators but also as role models, guides, and motivators in instilling discipline values. The main strategies applied include exemplifying (always arriving on time and dressing neatly), positive habituation (such as group prayers and cleanliness duties), and the use of educational rewards and reprimands. The challenges faced include the differing family beckgrounds of students that do not support school discipline and the varying characters of students. These challenges are addressed through intensive communication with parents and individual approaches. The conclusion emphasizes that the susses of instilling discipline is greatly determined by the teachers’ role modelling, consistency, and commitment in creating a strong culture of discipline